Developing Learner Autonomy Through Project Work in an ESP Class - Martha Isabel Díaz Ramírez (Asociación Colombiana de Profesores de Ingles, 2014)
This article presents the findings of an action research study on developing learner autonomy through project work in an English for Specific Purposes class. The study was conducted at a Colombian regional and public university with environmental engineering undergraduates. The instruments for data collection were field notes, semi-structured interviews, questionnaires, students' artifacts, and video recordings. The results revealed that learner autonomy could be developed by means of cooperative work in order to achieve common interests and support each other. Students also displayed self-regulation in regard to facing failures through learning strategies; furthermore, this study showed how intrinsic motivation implies the desire for accomplishment and knowledge to fulfill a learning goal.